Learning to be literate : the development of spoken and written language - Garton, Alison F., 1950-; Pratt, Chris (Oxford, UK ; New York, NY : Blackwell, 1998)
Literacy; Explanations of Spoken Language Development; Social interaction and the development of language; ...
Keywords: Literacy; Written communication; Language acquisition; Children language; Children -- Language; Literacy; Language acquisition; Written communication -- Study and teaching